A Comparison of Pancreatic Islet Purification using Iodixanol with University of Wisconsin Solution and with Na-Lactobionate and Histidine Solution. (6th June 2018) - Nakashima, Yoshiki; Miyagi-Shiohira, Chika; Ebi, Nana; Hamada, Eri; Tamaki, Yoshihito; Kuwae, Kazuho; Kobayashi, Naoya; Saitoh, Issei; Watanabe, Masami; Kinjo, Takao; Noguchi, Hirofumi
Purification of pancreatic islets is an important step in islet isolation for islet transplantation. In this study, to investigate how a solution composed mainly of Na-lactobionate and histidine (HL) influences the purification of islets, iodixanol was added to a purified solution for porcine islet isolation. A solution (IU) made by adding iodixanol to University of Wisconsin solution and a solution (IHL) made by adding iodixanol to HL solution were used to evaluate the islet isolation performance. We noted no significant differences between the two purification methods with regard to the islet yield, survival rate or purity, score, or stimulation index. These results show that IHL solution is as useful as IU solution for islet purification.